ARTISTIC COMMUNICATION BULLYING THE CONCEPT OF ALIENATION IN PRUSDIANTO'S TANIA ANDI THEATER PERFORMANCE - Nurabdiansyah, Nurabdiansyah; Saputra, Andi Taslim; Hamka, Dwi Wahyuni (JURNAL PAKARENA, 2024)
The relationship between theater and everyday life seems distant, barren, and isolated as a science. But as a performance, apart from being a creative medium that can channel artistic communication, it must also be close to the community. This mission was hinted at in Tania Andi's performance which initiated Brecht's concept of alienation. This research focuses on Tania Andi's performance which was staged at the Societet de Harmoni Arts Building in Makassar City at the South Sulawesi Student Theater Festival. The phenomenon of artistic communication is studied in this research using Roland Barthes' semiotic theory. This research aims to describe the semiotic meaning related to artistic communication which implies the meaning of bullying. The research method uses a qualitative approach with the research object being the Tania Andi Karya Prusdianto performance produced by the FBS UNM Literature Workshop. Interviews with actors and directors are primary data sources, while secondary data sources are literature studies and searches of several articles on the internet that are related to the research object. As a result, these attitudes and traits are certainly the result of responding negatively to our failure to deal with events and this becomes a symptom of bullying that appears verbally, physically and psychologically. These three forms of bullying emerged in the phenomenon of Tania Andi's performance with a performance that was conceptualized as alienation.